ENHANCING THE ECONOMIC AND HEALTH BENEFITS OF BLACKBERRY GROWN IN SOILLESS CULTURE BY FOLIAR APPLICATION OF POTASSIUM SULFATE: ENHANCING THE ECONOMIC AND HEALTH BENEFITS OF BLACKBERRY GROWN IN SOILLESS CULTURE BY FOLIAR APPLICATION OF POTASSIUM SULFATE (Iraqi Journal of Market Research and Consumer Protection, 2026)
Blackberry plant is an important subject for scientific research because of their economic importance and their high content of nutrients and antioxidants essential for human health.   The study was conducted at Research Station A, affiliated with the College of Agricultural Engineering Sciences, University of Baghdad, during the 2022-2023 agricultural season, aiming to improve the vegetative growth of the thornless blackberry variety grown in soilless cultivation systems using organic substrate from local plant waste (licorice root) (C3) and imported coconut waste (C2) compared to field soil (C1). as well as foliar application of Potassium sulfate (S) at three concentrations (0, 2.5, 5) g l-1, with 5 sprays every 20 days in a factorial experiment designed with complete randomized blocks and three replicates. The averages of the treatments were compared using the least significant difference (L.S.D.) test at a probability level of 5%. The results indicated that the treatment with cocopeat substrate and 5 g l-1 of potassium sulfate (C2S2) had the highest concentrations of nitrogen, phosphorus, total carotenoids, and total phenols at 2.497%, 0.530%, 537.44, and 10.62 mg 100g-1, respectively. Meanwhile, the treatment C2S1 excelled in plant height at 228.31 cm, single leaf area at 45.26 cm², and number of lateral branches at 5.31 branch shrub-1. The plants in the licorice root substrate with 5 g l-1, of potassium sulfate (C3S2) showed the highest concentration of sulfur at 1.2% and chlorophyll at 173.69 mg 100g-1 fresh weight, while the treatment C3S1 had the highest potassium concentration at 1.982% and a number of lateral branches at 5.31 branch shrub-1.